Cutaneous Manifestations in Obese Patients Attending Outpatient Department of a Tertiary Care Hospital - Pandit, Shashwata Raj; Neupane, Saraswoti (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Introduction: Obesity can have many effects on skin physiology. It is involved in dermatologic diseases like acanthosis nigricans, acrochordons, keratosis pilaris, hirsutism, and striae distensae. Objectives: To determine the proportion of various cutaneous manifestations in obese patients. Materials and Methods: This cross-sectional study was conducted at the Outpatient Department of Dermatology in a tertiary care hospital. Any patients over 18 years old with a BMI greater than or equal to 30 kg/m2 attending the dermatology OPD were included. The history-taking and examination were done, and the preformed proforma was completed. Statistical analysis was done using Microsoft Excel 2016 and SPSS Version 20.0 for Windows. Results: Our study included 226 patients. The mean age of patients in our study was 37.45± 13.60 years. There were more females than males in our study. The mean BMI of patients in our study was 32.09±1.81. According to BMI, most patients fell into grade I obesity (89.4%), followed by grade II obesity with 10.6%, and there were no patients with grade III obesity. Acrochordons was the most common dermatosis seen in the study, followed by acanthosis nigricans. The dermatoses that showed a statistically significant relationship with obesity grades were plantar hyperkeratosis (P = 0.001) and lymphoedema (P = 0.0036). Conclusion: Skin diseases are so common among obese patients that they can be considered a marker for obesity.